2019
DOI: 10.1155/2019/5813985
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Are Involved in the Development of Gastric Cancer and Gastric Cancer-Related Depression through ABL1-Mediated Inflammation Signaling Pathway

Abstract: Background. The mechanisms of crosstalk between depression and gastric cancer (GC) remain ill defined. Given that reactive oxygen species (ROS) is involved in the pathophysiology of both GC and depression, we try to explore the activities of ROS in the development of GC and GC-related depression. Methods. 110 patients with newly diagnosed GC were recruited in our study. The clinical characteristics of these patients were recorded. Inflammation and oxidative stress markers were detected by ELISA. The depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…A study elucidates that depression plays a role in enhancing the progression of hepatocellular carcinoma in mice via increasing programmed death 1 (PD-1) level regulated by glucocorticoids in tumor infiltrating natural killer (NK) cells [24]. Another study reveals that depression correlates with worse clinical outcome in gastric cancer patients, and the in vivo and in vitro experiments disclose that gastric cancer-related depression involves the participation of reactive oxygen species via the ABL1-modulated inflammatory pathway [25]. In addition, a previous study illustrates that anxiety and depression play a role in mediating the correlation of chemotherapy-induced peripheral neuropathy with fatigue in colorectal cancer patients; however, this study also states that this needs more experimental evidence to validate [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study elucidates that depression plays a role in enhancing the progression of hepatocellular carcinoma in mice via increasing programmed death 1 (PD-1) level regulated by glucocorticoids in tumor infiltrating natural killer (NK) cells [24]. Another study reveals that depression correlates with worse clinical outcome in gastric cancer patients, and the in vivo and in vitro experiments disclose that gastric cancer-related depression involves the participation of reactive oxygen species via the ABL1-modulated inflammatory pathway [25]. In addition, a previous study illustrates that anxiety and depression play a role in mediating the correlation of chemotherapy-induced peripheral neuropathy with fatigue in colorectal cancer patients; however, this study also states that this needs more experimental evidence to validate [26].…”
Section: Discussionmentioning
confidence: 99%
“…Second, anxiety and depression also induce many physical symptoms, such as fatigue, insomnia, and change of weight as well as appetite; these all contribute to a worse physical function and may interfere with the physical health of prostate cancer patients [31,32]. Third, anxiety and depression may aggregate the disease in prostate cancer patients via affecting several biological processes or pathways, such as regulating the tumor infiltrating NK cells and reactive oxygen species [24][25][26][27]. In the future, the status of anxiety and depression may be useful in optimizing the prognosis prediction in surgical prostate cancer patients; however, this should be validated by more highquality trials or large-scale cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“… [ 166 ] Gastric cancer Mouse ROS-activated ABL1 mediates inflammation through regulating NF-κB1 and STAT3, which subsequently leads to the development of GC and GC-related depression. [ 167 ] Gastric cancer Mouse Gastrin inhibited GC growth and enhanced the suppression of GC by cisplatin in mice or PGC cell culture models through activating the ERK-P65-miR23a/27a/24 axis or its components. [ 168 ] Gastric cancer Mouse LH inhibited tumorigenicity in gastric cancer through down-regulating the expression of MCL1.…”
Section: Patient-derived Tumor Xenograft (Pdx) Modelmentioning
confidence: 99%
“…Recently, studies have shown that the pathogenesis of hippocampal lesions and neuronal cell death in patients with depression might be related to the explosive activation of inflammatory reactions [1]. The "cytokine theory" suggests that stress-stimulated or over-activated immune systems produce inflammatory cytokines and play an important role in the pathogenesis of depression [2], which have been confirmed by clinical trials [3][4][5] and animal experiments [6,7]. Therefore, anti-inflammatory treatment for reducing the hippocampal inflammatory response and improving hippocampal function have become a new target for the prevention and treatment of depression.…”
Section: Introductionmentioning
confidence: 97%